Saudi women's perspectives on postpartum depression - Alsulami, Asmahan; Orabi, Abeer; Timraz, Shahrazad (Frontiers in Global Women's Health, 2024)
Introduction Postpartum depression (PPD) is a serious disorder that affects women worldwide, making it a crucial public health concern and one of the most prevalent childbirth complications. Assessing the perspectives of Saudi women towards PPD is essential for addressing the issue and developing effective solutions. This study aimed to assess the knowledge and attitude of Saudi women about PPD in King Abdulaziz Medical City, Western Region. Methods This study employed a descriptive cross-sectional research design and included 226 women recruited through convenience sampling at the Obstetrics and Gynaecology Outpatient Department in King Abdul-Aziz Medical City, Jeddah. Data were collected using a structured questionnaire with 3 main sections: socio-demographic characteristics, knowledge regarding risk factors and symptoms of PPD, and attitude about PPD. Results The mean score (SD) of the knowledge scale was 31.8 (6.2) with 53.5% of participants having a good level of knowledge about PPD. The mean score (SD) of the attitude scale was 27.1 (2.8) with 47.3% of participants having a positive attitude towards PPD. Significant differences were identified in the knowledge scale, where women who were postgraduates, working in the health sector and unpregnant scored higher in the knowledge scale compared to others (P = .008, P = .02, & P = .008, respectively). Discussion The findings of this study indicate that women's knowledge about PPD was generally good; however, many of them held negative attitudes towards PPD. These findings underscore the importance of proper education to improve mental health literacy and address prejudices and negative stereotypes related to PPD among Saudi women.